Effect of Self–Regulated Learning Strategies on Secondary School Students’ Performance in Home Economics Education - Ihensekhien, Isoken; Salami, L. I (Richtmann Publishing, 2012)
This study investigated if using self-regulated learning strategies could promote students learningperformance in Home Economics. A quasi-experimental design was used to examine the effectiveness of ateaching intervention in achieving the goals of learning using experiment group (N = 51) and controlgroup (N = 54). A pre-test was administered to both groups to determine their entry characteristic; astandardized aptitude test was also administered to both groups to determine their intelligent quotient(I.Q).At the end of the treatment which lasted for eight weeks, a post-test was given to both groups, todetermine the effect of treatment. All hypotheses were tested at 0.05 level of significance. The studyrevealed that the experimental group scored significantly higher on measures reflecting self-regulatedlearning process in their learning experience than the control group, (Mean= 28.80 experimental) (Mean =26.52 control). There was no significant difference in performance in academic ability of student with lowand high IQ exposed to self-regulated learning ( P = .336). The study revealed that there was a significanteffect of treatment (method) on students' achievement in Home Economics, with no significant difference inthe performance of students; The study thus recommended among others that teachers should encouragethe use of self-regulated learning method by student in studying Home Economics with better achievement.